2010
DOI: 10.1007/s12274-010-1035-z
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis and strong near-infrared upconversion luminescence of poly(acrylic acid)-functionalized YF3:Yb3+/Er3+ nanocrystals

Abstract: This paper describes the synthesis of new upconverting luminescent nanoparticles that consist of YF 3 :Yb 3+ /Er 3+ functionalized with poly(acrylic acid) (PAA). Unlike the upconverting nanocrystals previously reported in the literature that emit visible (blue-green-red) upconversion fluorescence, these as-prepared nanoparticles emit strong near-infrared (NIR, 831 nm) upconversion luminescence under 980 nm excitation. Scanning electron microscopy, transmission electron microscopy, and powder X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…However, the background autofluorescence in traditional fluorescence imaging techniques significantly limits the imaging sensitivity, especially for in vivo imaging in which the tissues and food residues exhibit strong background fluorescence [6]. In the past few years, studies on upconversion nanoparticles (UCNPs), usually containing lanthanide ions (Ln 3+ ), have grown rapidly owing to their wide applications in solidstate lasers, three-dimensional flat-panel displays, low-intensity infrared (IR) imaging, bioprobes, and bioimaging [7][8][9][10][11][12][13][14]. Compared with traditional downconversion fluorescent dyes and QDs, near infrared (NIR)-to-visible upconversion optical bioprobes have a number of advantages.…”
Section: Introductionmentioning
confidence: 99%
“…However, the background autofluorescence in traditional fluorescence imaging techniques significantly limits the imaging sensitivity, especially for in vivo imaging in which the tissues and food residues exhibit strong background fluorescence [6]. In the past few years, studies on upconversion nanoparticles (UCNPs), usually containing lanthanide ions (Ln 3+ ), have grown rapidly owing to their wide applications in solidstate lasers, three-dimensional flat-panel displays, low-intensity infrared (IR) imaging, bioprobes, and bioimaging [7][8][9][10][11][12][13][14]. Compared with traditional downconversion fluorescent dyes and QDs, near infrared (NIR)-to-visible upconversion optical bioprobes have a number of advantages.…”
Section: Introductionmentioning
confidence: 99%
“…As a good example, therefore, Wang et al reported on the upconversion NPs that emit NIRF luminescence -831 nm by using excitation of 980 nm -to minimize the absorption problems. 60 In summary, optical imaging has various advantages, including high sensitivity, low cost, short acquisition time of images, and safety. While it is true that NIR fluorophores improve tissue-penetration depth, the depth is not still sufficient to overcome a big hurdle for human in vivo imaging.…”
Section: +mentioning
confidence: 99%
“…When judiciously coated, some YF 3 :Yb 3 + /Er 3 + NPs lead to upconversion luminescence in the NIR (831 nm) rather than in the visible, which enables a greater penetration of the light [141] . Other examples include core@shell NdF 3 @ SiO 2 ( α -NaYbF 4 :Tm 3 + )@CaF 2 , NaGdF 4 :Nd 3 + @NaGdF 4 NPs, which also have excitation and emission in the NIR range and efficient deep-tissue imaging of small animals [133,142] .…”
Section: Upconverting Nanomaterialsmentioning
confidence: 99%